De iconografie van moderne heiligen. Op zoek naar aanzetten voor een nieuwe typologie - Tongeren, Louis van (Jaarboek voor liturgieonderzoek, 2003)
In the past decades there has been a paradoxical development of rise and fall in the position of the saint in the Church and in culture, and in the role that the saint plays in the life of the faithful. However, besides a decline and a revival of the traditional cult of saints a new type of saint seems to be appearing, the modern saint, who only partly fulfils the traditional qualifications of sanctity or in some cases not at all. One of the places in which these modern saints can be found is in iconography. The modern saint is typified using four recent iconographical depictions that can be found in the Anna Church in Heerlen, the Bavo cathedral in Haarlem, the Dom in Utrecht and St. Gregory’s in San Francisco. The criteria for canonisation maintained by the Church do not seem to apply. In many cases it is not primarily the people depicted who are important, but the values they symbolise. Modern saints function mainly as models. They are neither mediators nor advocates, but prophetic representatives of what is right and just, of spirituality and mysticism. Modern saints are not automatically examples of faith, but models in whose life God’s goodness was or is manifested. They are not necessarily from Christian tradition; examples of sanctity can be found outside the Church too. Moreover, the type of the modern saint seems also to be acceptable within Reformed Churches. This probably has to do partly with the lack of cultist customs surrounding the modern saint where it is celebration and not commemoration that is most important. The modern saint represents a different type of sanctity that is strongly connected to time and culture, and because of this regularly demands an update. Sanctity appears to be of a transitory nature.